Nursing taxonomies in hospital discharge planning: a quasi-experimental study - Dayanna Machado Pires Lemos; Priscilla Ferreira Saldanha; Laura Fonseca Vieira; Karina de Oliveira Azzolin
ABSTRACT Objective: to evaluate the effect of implementation of hospital discharge planning based on the taxonomies of NANDA-International, nursing interventions classification (NIC) and nursing outcomes classification (NOC) for patients with heart failure (HF) or diabetes mellitus (DM). Methods: quasi-experimental quantitative study conducted in a public university hospital located in the state of Rio Grande do Sul, Brazil. Convenience sampling included 28 adult patients hospitalized for HF or DM with the nursing diagnosis Ineffective Health Management (00078), who received the following nursing interventions: Teaching: Disease Process, Teaching: Prescribed Medication and Teaching: Prescribed Diet. Before and after the intervention, the following nursing outcomes were evaluated : Knowledge: Diabetes Management and Knowledge: Heart Failure Management. Results: the score of the nursing outcome Knowledge: Heart Failure Management went from 2.05±0.28 to 2.54±0.30 (P=0.002), and of the nursing outcome Knowledge: Diabetes Management went from 2.61±0.55 to 3.21±0.57 (P=0.000). Conclusion: discharge planning based on the NIC improves the NOC score and may interfere in the health outcomes.